Methionine represses the autophagy of gastric cancer stem cells via promoting the methylation and phosphorylation of RAB37. Issue 20 (17th October 2020) - Xin, Lin; Li, Shi-Hao; Liu, Chuan; Zeng, Fei; Cao, Jia-Qing; Zhou, Li-Qiang; Zhou, Qi; Yuan, Yi-Wu
ABSTRACT: This study focused on the role of methionine (MET) in the autophagy of gastric cancer stem cells (GCSCs) and aims to elaborate its regulatory mechanism. In the present study, the GCSCs were isolated from human gastric cancer cell lines using an anti-CD44 antibody, and then cultured in MET + homocysteine (HCY) − or MET − HCY + medium. In MET + HCY – treated GCSCs, autophagy was suppressed, the methylation and phosphorylation of RAB37 were elevated, and miR-200b expression was down-regulated. Lentiviral vector (LV-) carrying methionine-γ lyase (an enzyme that could specifically lyse MET; Metase) promoted autophagy, reduced the methylation and phosphorylation of RAB37, and up-regulated miR-200b expression in MET + HCY – -treated GCSCs. Then, we found that miR-200b suppressed the expression of protein kinase C α (PKCα), a protein that could inactivate RAB37 through promoting its phosphorylation. LV-Metase down-regulated RAB37 phosphorylation via miR-200b/PKCα, thus promoting the RAB37-mediated autophagy and suppressing cell viability in MET + HCY – treated GCSCs. Finally, the in vivo study proved that LV-Metase treatment inhibited tumor growth through up-regulating RAB37 expression. In conclusion, MET suppressed RAB37 expression via enhancing its methylation and suppressed RAB37 activity via miR-200b/PKCα axis, thus repressing RAB37-mediated autophagy in GCSCs. The supplementation of Metase lysed MET, thus inducing the autophagy of GCSCs and inhibiting tumor growth. GRAPHICAL ABSTRACT: